The Concept of IPAS with the LSQ Learning Method: Question Card Media for Primary School Students - Nisa, Fadilatun; Fiteriani, Ida; Ningrum, Ayu Reza (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The background of this research is the low participation of students in the learning process, which has an impact on poor conceptual understanding. Therefore, this research aims to improve students' conceptual understanding through the application of the Learning Start with a Question (LSQ) strategy assisted by Question Card Media in the subject of IPAS. This type of research uses the Classroom Action Research model. This research took place in Class V State Elementary Madrasah 7 Bandar Lampung. The research took place in two cycles consisting of the planning stage, implementation of actions, observation, and reflection on the material of Knowing the Location and Nature of Indonesia. The findings of the study indicated that the application of the LSQ method assisted by question cards was effective in improving students' conceptual understanding in IPAS learning. There was a significant increase in students' conceptual understanding from cycle I to cycle II, with the level of activity reaching a peak of 92.5% in cycle II. Students' understanding also experienced a positive increase from cycle to cycle. The number of students who achieved the Learning Objectives Achievement Criteria increased in each cycle, with cycle 1 at 81% increasing to 92.5% in cycle II. The reflection and adjustment process in each cycle made a positive contribution to the success of the learning method. The implications of this study include the potential application of the Learning Starts With A Question method assisted by Question Card media to improve students' understanding, participation, and activeness in IPAS learning.